Potential Application of Yokukansan as a Remedy for Parkinson's Disease. (20th December 2018) - Jang, Jung-Hee; Jung, Kyungsook; Kim, Joong-Sun; Jung, Inchul; Yoo, Horyong; Moon, Changjong
Abstract : Parkinson's disease (PD), the second most common progressive neurodegenerative disorder, is characterized by complex motor and nonmotor symptoms. The clinical diagnosis of PD is defined by bradykinesia and other cardinal motor features, although several nonmotor symptoms are also related to disability, an impaired quality of life, and shortened life expectancy. Levodopa, which is used as a standard pharmacotherapy for PD, has limitations including a short half-life, fluctuations in efficacy, and dyskinesias with long-term use. There have been efforts to develop complementary and alternative therapies for incurable PD. Yokukansan (YKS) is a traditional herbal medicine that is widely used for treating neurosis, insomnia, and night crying in children. The clinical efficacy of YKS for treating behavioral and psychological symptoms, such as delusions, hallucinations, and impaired agitation/aggression subscale and activities of daily living scores, has mainly been investigated in the context of neurological disorders such as PD, Alzheimer's disease, and other psychiatric disorders. Furthermore, YKS has previously been found to improve clinical symptoms, such as sleep disturbances, neuropsychiatric and cognitive impairments, pain, and tardive dyskinesia. Preclinical studies have reported that the broad efficacy of YKS for various symptoms involves its regulation of neurotransmitters including GABA, serotonin, glutamate, and dopamine, as well as the expression of dynamin and glutamate transporters, and changes in glucocorticoid hormones and enzymes such as choline acetyltransferase and acetylcholinesterase. Moreover, YKS has neuroprotective effects at various cellular levels via diverse mechanisms. In this review, we focus on the clinical efficacy and neuropharmacological effects of YKS. We discuss the possible mechanisms underpinning the effects of YKS on neuropathology and suggest that the multiple actions of YKS may be beneficial as a treatment for PD. We highlight the potential that YKS may serve as a complementary and alternative strategy for the treatment of PD.